Time series modeling of Nigeria external reserves - Iheanyichukwu S. Iwueze; Eleazar C. Nwogu; Valentine U. Nlebedim (CBN Journal of Applied Statistics, 2013)
This paper discusses the levels and trend of external reserves in Nigeria. The relevance of this lies in the fact that it could help to monitor the reserves and throw early warning signal about any economic crisis. Monthly data on Nigeria external reserves for the period January 1999 to December, 2008 derived from the 2008 CBN Statistical Bulletin was analyzed using ARIMA model. Results of the analyses show that (i) the data requires logarithmic transformation to stabilize the variance and make the distribution normal (ii) the appropriate model that best describes the pattern in the transformed data is the Autoregressive- Integrated Moving Average process of order (2,1,0). This model is recommended for use until further analysis proves otherwise.
Keywords: C22; C51; C53; F30; F31; 330; External Reserves; Autoregressive Process; Transformation; Variance Stability; Payment Imbalances